China's one-child policy and ‘the mystery of missing women': Ethnic minorities and male-biased sex ratios - Bulte, Erwin; Heerink, Nico; Zhang, Xiaobo (Wiley, 2011)
Recent estimates suggest that as many as 40 million women are ‘missing’ in China. We exploit a special provision in the Chinese one‐child policy (OCP; allowing for preferential treatment of ethnic minority groups) to revisit the mystery of these missing women, and in particular to explore the contribution of China's OCP in distorting sex ratios. Our results imply that preference for boys is the main driver of the gender gap, and that the OCP is responsible for about half of it. This is true even before ultrasound technologies for prenatal gender determination were available. Not surprisingly, interaction between the OCP and ultrasound technologies has contributed to the gender gap.